More Than Skin Deep: Autophagy Is Vital for Skin Barrier Function - Sil, Payel; Wong, Sing-Wai; Martinez, Jennifer (Frontiers in Immunology, 2018)
The skin is a highly organized first line of defense that stretches up to 1.8m2 and is home to more than a million commensal bacteria.The microenvironment of skin is driven by factors such as pH, temperature, moisture, sebum level, oxidative stress, diet, resident immune cells, and infectious exposure. The skin has a high turnover of cells as it continually bares itself to environmental stresses. Notwithstanding these limitations, it has devised strategies to adapt as a nutrient-scarce site. To perform its protective function efficiently, it relies on mechanisms to continuously remove dead cells without alarming the immune system, actively purging the dying/senescent cells by immunotolerant efferocytosis. Both canonical (starvation-induced, reactive oxygen species [ROS], stress, environmental insults) and non-canonical (selective) autophagy in the skin have evolved to perform astute due-diligence and housekeeping in a quiescent fashion for survival, cellular functioning, homeostasis, and immune tolerance. The autophagic ‘homeostatic rheostat’ works tirelessly to uphold the delicate balance in immunoregulation and tolerance. If this equilibrium is upset, the immune system can wreak havoc and initiate pathogenesis. Out of all the organs, the skin remains under-studied in the context of autophagy. Here we touch upon some of the salient features of autophagy active in the skin.